Sistem Kontrol Lampu Dan Kipas Angin Dengan Google Assistant Berbasis IoT - Mardi Utomo, Vinsensius Alvianto; Mahendra, Christy; Lianawati, Yosita (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
Electricity usage in Indonesia has become an essential part of daily life, steadily increasing over the years. According to the Central Statistics Agency, per capita electricity consumption was 0.91 MWH in 2015, rising to 1.09 MWH in 2020. This upward trend can be curbed with technological advancements. In many buildings, lights and fans are manually controlled through switches. While suitable for small spaces, this method becomes inefficient and leads to energy wastage in larger buildings with multiple rooms, often going unnoticed. Additionally, the perception of electricity wastage varies among individuals, depending on their habits. To address this, a smart IoT-based system with Google Assistant control has been designed. The system employs NodeMCU ES8266 microcontroller, DHT11 sensors, 2-channel relay, USB fans, 5W light bulbs, Google Home, Google Assistant, and Sinric Pro. Tested in a black box scenario, the system achieved an accuracy rate of 83%. The DHT11 sensor exhibited a maximum error of 5% for temperature readings and 1% for humidity. The overall error for DHT11 sensor readings ranged from 13% to 8%.